Farm Partnership between Farmers and the Company in Production and Marketing of Vegetables Commodity - Devy Anggita Puspitaningrum; Siwi Gayatri (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2019)
Farm partnership model between farmers and industries is expected to give advantages in many aspects such as economic, technical, and social. The research aims to analyze the farm partnership model between vegetable farmers and PT. Bumi Sari Lestari company. Primary data were collected using an interview. Secondary data were gotten by documentation. The data were analyzed by the analytical technique. The result shows that the type of partnership between farmers and the company is Inti-Plasma model based on Memorandum of Understanding (MoU) containing the clause if farmers were not able to provide sufficient vegetable, the company would buy directly from the market. The vegetables bought by the industry would be cultivated by the farmer and controlled by industry. There are many issues that have to be solved by the farmers and the company. First, farmers will choose a traditional ceremony instead of harvesting the plants. Hence, the vegetables will get rotten. Farmers will prefer to sell their vegetables to the market instead of bringing it to the company when the price gets high in the normal market. Vegetables will get rotten easily during the transportation process to the company. The last is the company needs to make an agreement with the farmers to decide optimal production based on the farm size in order to avoid over production.  JEL Classification: D19, J54, Q12